22q and two: 22q11.2 deletion syndrome and coexisting conditions. Issue 10 (23rd September 2018) - Cohen, Jennifer L.; Crowley, Terrence B.; McGinn, Daniel E.; McDougall, Carey; Unolt, Marta; Lambert, Michele P.; Emanuel, Beverly S.; Zackai, Elaine H.; McDonald‐McGinn, Donna M.
Abstract : 22q11.2 deletion syndrome (DS) is the most frequent copy number variant (CNV) affecting ~1/1, 000 fetuses and ~1/2, 000–4, 000 children, resulting in recognizable but variable findings across multiple organ systems. Patients with atypical features should prompt consideration of coexisting diagnoses due to additional genome‐wide mutations, CNVs, or mutations/CNVs on the other allele, unmasking autosomal recessive conditions. Importantly, a dual diagnosis compounds symptoms and impacts management. We previously reported seven patients with 22q11.2DS and: SCID, Trisomy 8 mosaicism, Bernard‐Soulier, and CEDNIK syndromes. Here we present six additional unreported patients with 22q11.2DS and concurrent diagnoses. Records on 1, 422 patients with 22q11.2DS, identified via FISH, microarray, or MLPA, followed in our 22q and You Center at the Children's Hospital of Philadelphia (CHOP) were reviewed to identify a dual diagnosis. In addition to our seven previously reported cases, we identified an additional six with 22q11.2DS and another coexisting condition identified via: molecular/cytogenetic studies, newborn screening, coagulation factor studies, or enzyme testing; these include CHARGE syndrome ( CHD7 mutation), cystic fibrosis, a maternally inherited 17q12 deletion, G6PD deficiency, von Willebrand disease, and 1q21.1 deletion, resulting in an incidence of dual diagnoses at our center of 0.9%. The range of dual diagnoses identified in our cohort is notable, medically actionable, and may alter long‐term outcome and recurrence risk counseling. Thus, our findings may support testing patients with 22q11.2DS using a combination of microarray, mutational analysis of the other allele/WES, to ensure appropriate personalized care, as formulating medical management decisions hinges on establishing the correct diagnoses in their entirety.